Early Improvement in Postoperative Clinical Outcomes without Patellar Resurfacing in Patella-Friendly Design of Medial Pivot TKA - Cooper, Leo; Owen, Brewer; Soeno, Tatsuya; Wahl, Stephen; Stambough, Jeffrey B.; Barnes, C. Lowry; Mears, Simon C.; Stronach, Benjamin M. (The Journal of Knee Surgery, 2024)
There is continued debate about the efficacy and indications for patellar resurfacing in total knee arthroplasty (TKA), especially with the emergence of patella-friendly designs. This study aimed to compare the postoperative outcomes in patients undergoing TKA with or without patellar resurfacing using the same implant design. This is a retrospective cohort study of patients who underwent TKA including those with patellar resurfacing (PR group) and those without (NPR group). Demographic data included age, gender, side of surgery, operative time, and body mass index (BMI). Outcomes included preoperative, 2-week, 6-week, and 1-year postoperative Knee Injury and Osteoarthritis Outcome Score and Joint Replacement (KOOS, JR) values along with knee range of motion (ROM). Postoperative complications were recorded. The power analysis with a large effect size indicated that a minimum sample size of 54 was required for Student's t-test and 34 for the paired t-test. A total of 90 medial pivot (MP) TKA were included in this study. There were 30 knees in the PR group and 60 in the NPR group. There was no significant difference between the groups for all demographic data, preoperative and postoperative ROM, and KOOS, JR values at all time points (p > 0.05 for all variables). The KOOS, JR significantly improved in the NPR groups at 2 weeks, 6 weeks, and 1 year postoperatively when compared with the preoperative score and at 6 weeks and 1 year postoperatively in the PR group (p < 0.01). No revisions related to the patellofemoral joint were observed in patients initially undergoing patellar resurfacing. One patient in the NPR group required secondary patellar resurfacing. The patella-friendly MP TKA yielded favorable postoperative outcomes, with or without patellar resurfacing. Improvements in KOOS, JR were observed earlier in the NPR group when compared with the PR group, suggesting that patellar resurfacing may not always be necessary for modern TKA designs.Level of Evidence Retrospective cohort study, Level III.
Keywords: patellar-friendly design; patella; patellar resurfacing; total knee arthroplasty; medial pivot